2014
DOI: 10.1002/2014gl062020
|View full text |Cite
|
Sign up to set email alerts
|

Van Allen Probe observations of periodic rising frequencies of the fast magnetosonic mode

Abstract: Near simultaneous periodic dispersive features of fast magnetosonic mode emissions are observed by both Van Allen Probes spacecraft while separated in magnetic local time by~5 h: Probe A at 15 and Probe B at 9-11 h. Both spacecraft see similar frequency features, characterized by a periodic repetition at~180 s. Each repetition is characterized by a rising frequency. Since no modulation is observed in the proton shell distribution, the plasma density, or in the background magnetic field at either spacecraft we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
91
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(110 citation statements)
references
References 23 publications
(31 reference statements)
13
91
4
Order By: Relevance
“…Such a modulation phenomenon appears to be not rare in the dayside magnetosphere following the solar wind dynamic pressure fluctuations. Another interesting feature of Figure 3 is the falling frequency magnetosonic emissions in each cycle, different from the previously reported rising frequency magnetosonic emissions (Boardsen et al, 2014;Fu et al, 2014). Compared to the interval of Figure 3, the intervals of Figures S5 and S6 with the weaker ULF pulsations allowed the less obvious quasiperiodic variations in the whistler-mode power.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Such a modulation phenomenon appears to be not rare in the dayside magnetosphere following the solar wind dynamic pressure fluctuations. Another interesting feature of Figure 3 is the falling frequency magnetosonic emissions in each cycle, different from the previously reported rising frequency magnetosonic emissions (Boardsen et al, 2014;Fu et al, 2014). Compared to the interval of Figure 3, the intervals of Figures S5 and S6 with the weaker ULF pulsations allowed the less obvious quasiperiodic variations in the whistler-mode power.…”
Section: Discussioncontrasting
confidence: 70%
“…The other involves the modulation of wave instabilities by the accompanied ultralow-frequency (ULF) waves (Helliwell, 1965;McPherron et al, 1968;Sato & Fukunishi, 1981;Sato et al, 1974): (1) the ULF pulsations modulate the background parameters and the resonant particle distributions; (2) the wave instabilities are cyclically turned on and off. Although the ULF pulsations were found to substantially modulate the linear growth rates of whistler-mode emissions in several events (W. Li et al, 2011;Manninen et al, 2010), there are still the quasiperiodic whistler-mode emissions occurring without the observable ULF pulsations (Boardsen et al, 2014;Kitamura et al, 1969;Němec et al, 2014;Sato et al, 1974;Titova et al, 2015;Tsurutani & Smith, 1974) or with the ULF pulsations of the essentially different periods (Němec et al, 2015). In contrast, there is evidence both for and against the latter scenario.…”
Section: Introductionmentioning
confidence: 95%
“…Boardsen et al [2014] argued, as we did in the introduction, that the most favorable wave growth will be in the azimuthal direction, because this configuration allows a ray to remain in resonance with the source for a much longer time period. The rays are launched only with the perpendicular component of their wave vector in the azimuthal direction.…”
Section: Discussionmentioning
confidence: 76%
“…Inside the plasmapause they are observed at all magnetic local times (MLT), while outside the plasmapause they occur more frequently on the day side. Studies show that the power in these waves increases with AE* [Meredith et al, 2008], where AE* is the peak AE index over the previous 3 h. Recently quasi-periodic modulation of these waves has been reported [Fu et al, 2014;Boardsen et al, 2014;Němec et al, 2015]. They typically have been observed within magnetic latitudes (MLAT) of ±15° [Kasahara et al, 1994] but have been reported outside this range [e.g., Tsurutani et al, 2014;Posch et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…These emissions are composed of a complex system of many spectral lines with spacing ranging from a few hertz to a few tens of hertz, linked to ion cyclotron frequencies in local or distant sources [Gurnett, 1976;Santolík et al, 2002a;Ma et al, 2014]. Superposed rising tone quasiperiodic structures can also occasionally occur [Fu et al, 2014;Boardsen et al, 2014;Němec et al, 2015b].…”
Section: Introductionmentioning
confidence: 99%